Jaminan Kepastian Hukum Balik Nama Didasarkan Kewarisan Tanpa Persetujuan Ahli Waris - Putera, Christoper; Lukito, Hilda (Universitas Ekasakti, 2023)
In order to provide definite guarantees according to law, land registration is carried out according to the provisions in Government Regulation no. 24/1997. The act of transferring a plot of land due to inheritance is recorded, a death certificate is completed, a statement of land rights if it has been registered, a deed of information on the party entitled to inheritance, registered at the Land Office (Kantah). The recording of the act of transferring a plot of land due to inheritance without a certificate of inheritance being included is problematic for the party entitled to other inheritance. The research used a statutory approach and a case approach, and the conclusion was obtained: To provide definite guarantees according to the law, the act of transfer must be registered in Kantah for the purpose of changing the name of the information of rights as stipulated in Article 19 of the UUPA. The act of transferring due to inheritance must be submitted by the party entitled to inheritance in addition to information on land plot rights, including death certificates, certificates of information as parties entitled to inheritance as stated in PP No. 24/1997 in conjunction with ATR Ministerial Regulation/Head of BPN No. 16/2021. The act of transferring a plot of land due to inheritance without the consent of the party entitled to inheritance even though Kantah issues a statement of rights, does not provide a definite guarantee according to the law for someone whose name is recorded in the statement of rights.